Food choice in Megalobulimus paranaguensis (Gastropoda, Eupulmonata) - Miranda, Marcel Sabino; Correia, Lucas Vilas Boas [UNESP] (Taylor & Francis Ltd, 2020)
The biology of South American land snails, can be achieved if their eating habits and by extension their distribution in the environment is understood. The present study evaluates the food choices of Megalobulimus paranaguensis. In the laboratory, we tested whether M. paranaguensis prefers fresh or dry Malvaviscus flowers. Our results indicate that the species is herbivorous and that it has a preference for fresh flowers. This preference can be important to determine its distribution pattern in the environment.
Keywords: Land snail; preference; food consumption